The potential of CRL4DCAF1 and KSR1 as therapeutic targets in merlin-deficient meningioma - Rimmer, Jade Lyons (Neuro Oncol, 2018)
BACKGROUND: Merlin-deficient meningiomas are caused by mutations in the Neurofibromin 2 gene and occur in approximately 60% of sporadic meningiomas. Merlin loss is commonly associated with the genetic condition Neurofibromatosis type 2, leading to the development of multiple low grade tumours including schwannoma and meningioma. Currently, the only treatment for low grade meningioma is (radio)surgery therefore identification of novel drug targets is vital. Previous studies have shown that Kinase suppressor of Ras 1 (KSR1) is a potential therapeutic target in schwannoma and that the E3 ubiquitin ligase, CRL4DCAF1, binds to KSR1. The aim of this project is to investigate the interaction between CRL4DCAF1 and KSR1 to determine if targeting this protein complex in meningioma holds therapeutic value. METHODS: HEK293T cells were transfected with KSR1 constructs and interactions with CRL4DCAF1 were investigated by immunoprecipitation. Immunohistochemistry, cell fractionation and Western blot were used to analyse DCAF1 and KSR1 expression and localization in primary human meningioma. A shRNA construct was used to knock down DCAF1 and APS_2_79 was used to inhibit KSR1. RESULTS: KSR1 interacts via the N-term with DCAF1 and is ubiquitinated at the C-term in the NF+/+ model which may be DCAF1 dependent. Immunohistochemistry showed increased DCAF1 and KSR1 expression in Merlin-deficient meningiomas compared with normal meninges, whereas Western blot analysis showed variable protein expression. DCAF1 knockdown led to a reduction of nuclear pERK1/2 and a significant decrease in proliferation of meningioma cells but pERK1/2 and Cyclin D1 levels were unchanged. Combination of shDCAF1 and APS_2_79, a specific KSR1 inhibitor, reduced pERK and proliferation in both BenMen-1, a benign meningioma cell line and primary meningioma. Therefore, targeting both DCAF1 and KSR1 represents an attractive novel therapeutic strategy in meningioma.